Pré tratamento dentinário influência do condicionamento ácido, irradiação laser e hipermineralização na resistência ao cisalhamento de sistema adesivo multi uso - Gonçalves, Sérgio Eduardo de Paiva [UNESP] (1997)
The disadvantages generated by the acid etching of the dentin, such as an increase in its permeability, in the surface moisture and in the potential to denature the external dentinal collagen, the formation of a fragility zone and the citotoxicity of the adhesive monomers; which are all aggravated by the depth of the dentin, have stimulated new and different treatment philosophies of the dentin. The purpose of the present study, therefore, was to investigate the effects of three dentin treatments: laser irradiation, acid etching and hypermineralization, in the shear bond strength of the SMP Plus bonding system. Sixty bovine incisors were extracted and randomly selected immediatly alter the animal's death. They were kept frozen (-18°C) for no longer than 14 days. After buccal dentinal surface had been exposed, X-Rays were taken to control the dentin thickness. The specimens were separated into two groups: (1) Control, kept in distilled water at 4ºC; (2) Mineralized, kept in hypermineralized solution at 4°C for 14 days. Each group was divided into three sub-groups according to the type of dentin treatment used: group F - followed the manufacturer instructions (acid-etching + primer + bond), group AL (acid-etching + primer + bond + laser) and group LA (laser + (laser + acid-etching + primer + bond). A composite resin standard cylinder (Z100-3M) was bond to the dentinal surface and the shear bond strength performed on a Universal lnstron machine 4301, with 500 Kg load and at 0,5mm/min. speed. The analysis of variance (ANOVA) determined that the treatments influenced the shear bond strength values (p<0,05) with the following average shearing load at failure: AL (9,96 MPa), F (7,28MPa) e LA (4,87 MPa). The interaction between the two factors analyzed Group (control and mineralized) and treatment (F, AL, LA) also influenced the shear bond strength (p<0,05). The highest values were obtained...